KEY COMMITMENTS AND EXPECTATIONS FROM THE 2024 NATO SUMMIT IN WASHINGTON (Security Dialogues, 2025)
In the period from 9 until 11 July, 2024, the 75 anniversary Summit of the Headsof State and Government of the Alliance was held in Washington, in the conditions of aconventional threat to the security of the Alliance and in a time of war on the soil of Europe.NATO leaders discussed strategically important issues related to deterrence and defense,long-term support for Ukraine and cooperation with the Alliance’s global partners. Thefocus in strengthening the Alliance’s defense and deterrence is placed through “investingin new, modern high-end military capabilities” and “increasing the readiness of our forces,”(Stoltenberg, 2024) all underpinned by major increases in defence spending across theAlliance by supporting the increase in defense spending.I have suggested that at the Summit, we agree a big NATO role in coordinating and providingsecurity assistance and training for Ukraine,” he said. “I strongly believe that we need afirmer, stronger institutionalized structure for the support. Ad-hoc, short term, voluntaryannouncements are good – but in the long term, we need more predictable, stronger supportfor Ukraine. In relation to the support of Ukraine, NATO is expected to increase its role inthe coordinating and providing security assistance and training for Ukraine. According toStoltenberg, this implies the establishment of a “firmer, stronger institutionalized structure”that will ensure a more predictable and sustainable long-term support of Ukraine. Cooperationwith partners is crucial for security and stability because security is not only a regional issuebut also a global issue.
Keywords: NATO, Deterrence and Defence, Partners, Ukraine